Systematics and biogeography of the non‐viny grape relative Leea (Vitaceae). (20th November 2012) - Molina, Jeanmaire E.; Wen, Jun; Struwe, Lena
<x xml:space="preserve">Abstract</x> Leea, sometimes treated as the monogeneric family Leeaceae, is sister to the rest of the grape family, Vitaceae, but its systematics is poorly known. Phylogenetic relationships in Leea were reconstructed with parsimony and Bayesian methods using nuclear ribosomal sequences to assess species circumscriptions, morphological evolution and biogeography. The internal transcribed spacer secondary structure model for Leea facilitated homology assessments during sequence alignment. Nine morphological characters were mapped onto the phylogenetic tree. Four major clades in Leea were supported, with L. asiatica s.l. (=clade I) as the earliest diverging clade and having plesiomorphic free stamens. Clade II, which includes the prickle‐bearing species, is sister to clade III, which includes species with comparatively large flowers. Clade IV, sister to clade II + III, was resolved into four subclades. Each subclade included accessions of L. indica and L. guineensis intermixed with six other morphologically distinct species, showing the polyphyly of these two species as currently circumscribed. Flower colour, previously used to characterize species, was shown to be unreliable for species identification. Dating analyses estimated that Leea originated in Indochina in the Late Cretaceous (65–86.19 Mya, 95% highest posterior density). The members of the major clades later spread to India, Africa, Madagascar, South‐East (SE) Asia and tropical Australasia. Major species diversification occurred in the Neogene, when dynamic environmental and geological changes in SE Asia presented new ecological niches. © 2012 The Linnean Society of London, Botanical Journal of the Linnean Society, 2012, ●●, ●●–●●.